2012
DOI: 10.1371/journal.pone.0038743
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic Diagnosis of Lower Respiratory Tract Bacterial Infections Using Sputum Samples and Quantitative Loop-Mediated Isothermal Amplification

Abstract: Etiologic diagnoses of lower respiratory tract infections (LRTI) have been relying primarily on bacterial cultures that often fail to return useful results in time. Although DNA-based assays are more sensitive than bacterial cultures in detecting pathogens, the molecular results are often inconsistent and challenged by doubts on false positives, such as those due to system- and environment-derived contaminations. Here we report a nationwide cohort study on 2986 suspected LRTI patients across P. R. China. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Here, we have found that H. influenza was the leading bacteria responsible for the respiratory infections of the patients we have recruited in this study. Similar to our work, Kang et al (2012) reported that the most common respiratory bacterial infections are caused by H. influenzae, S. pneumoniae, respiratory syncytial virus and so on. Similar studies also demonstrated that the S. pneumoniae, Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Here, we have found that H. influenza was the leading bacteria responsible for the respiratory infections of the patients we have recruited in this study. Similar to our work, Kang et al (2012) reported that the most common respiratory bacterial infections are caused by H. influenzae, S. pneumoniae, respiratory syncytial virus and so on. Similar studies also demonstrated that the S. pneumoniae, Fig.…”
Section: Discussionsupporting
confidence: 90%
“…China) as described elsewhere. [56] A presumptive diagnosis of acute Mpinfection was made by a positive IgM result. Clinical characteristics of patients were also recorded.…”
Section: Methodsmentioning
confidence: 99%
“…[6] Nine respiratory viruses in BALF were detected using FTD respiratory pathogens 21 plus multiplex real-time polymerase chain reaction kit (Fast-track Diagnostics, Junglinster, Luxembourg). Meanwhile, the assay using conventional sputum culture for each patient was carried out.…”
Section: Methodsmentioning
confidence: 99%
“…A loop-mediated isothermal amplification system developed cooperatively by the Peking University People's Hospital and CapitalBio Corporation in China is currently being tested in clinical trials. 8 The bead-based suspension array (liquid chip) platform developed by the Luminex Corporation in the United States is a rapid, high-throughput system for multi-analyte detection. 4,5,[8][9][10][11] The system is based on polystyrene microspheres internally labeled with a unique dye combination.…”
Section: Introductionmentioning
confidence: 99%